2004
DOI: 10.1029/2003ja010234
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Data Assimilation Three‐Dimensional (IDA3D): A global, multisensor, electron density specification algorithm

Abstract: [1] With the advent of the Global Positioning System (GPS) measurements (from both ground-based and satellite-based receivers), the number of available ionospheric measurements has dramatically increased. Total electron content (TEC) measurements from GPS instruments augment observations from more traditional ionospheric instruments like ionospheric sounders and Langmuir probes. This volume of data creates both an opportunity and a need for the observations to be collected into coherent synoptic scale maps. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
271
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(286 citation statements)
references
References 34 publications
0
271
0
Order By: Relevance
“…Bust et al (2004) suggested the separation of the spatial covariance model into horizontal and vertical components to take the geometric anisotropy of the ionosphere, i.e., directionally dependent correlation lengths, into account. Yue et al (2007) and Shim et al (2008) confirmed this approach with the analysis of GPS and incoherent scatter radar observations revealing different correlation lengths in latitude, longitude and height direction.…”
Section: Spatial Covariance Model Of Electron Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bust et al (2004) suggested the separation of the spatial covariance model into horizontal and vertical components to take the geometric anisotropy of the ionosphere, i.e., directionally dependent correlation lengths, into account. Yue et al (2007) and Shim et al (2008) confirmed this approach with the analysis of GPS and incoherent scatter radar observations revealing different correlation lengths in latitude, longitude and height direction.…”
Section: Spatial Covariance Model Of Electron Densitymentioning
confidence: 99%
“…However, EDAM also deals with ionospheric radio occultation (IRO), ionosonde data and in situ electron density measurements; see Angling et al (2008). Bust et al (2004) developed a similar approach, the Ionospheric Data Assimilation ThreeDimensional (IDA3-D) technique based on 3-D variational data assimilation. Both EDAM and IDA3-D apply an exponential time covariance model to forecast the electron density state vector and its covariance matrix from one time step to the next.…”
Section: Introductionmentioning
confidence: 99%
“…A multiinput tomographic algorithm, named as Multi‐Instrument Data Analysis System (MIDAS) was built to enable the ingestion of multiple data sources (e.g., ground‐based GPS data, Low Earth Orbiter‐based GPS data, and ionosonde measurements) into the inversion to produce images of ionospheric electron density [ Mitchell and Spencer , 2003]. Bust et al [2004] developed an ionospheric imaging technique based on data assimilations—Ionospheric Data Assimilation Three‐Dimensional. A comprehensive review of ionospheric imaging is given in Bust and Mitchell [2008].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, IDA4D has been used to investigate the ionospheric response to major geomagnetic storms [Bust and Mitchell, 2008;Bust and Crowley, 2008], including the formation and evolution of SED. A complete mathematical derivation of the IDA4D algorithm can be found in Bust et al [2000Bust et al [ , 2004 and Bust and Datta-Barua [2012a]. One of the powerful features of IDA4D is that the inversion grid is user selectable and need not be regular.…”
Section: Ionospheric Data Assimilation Four-dimensionalmentioning
confidence: 99%
“…[11] Ionospheric Data Assimilation Four-Dimensional (IDA4D) [Bust et al, 2000] is a continuous-time, threedimensional imaging algorithm [Bust et al, 2004] routinely used to produce 4-D (time and space) ionospheric electron density specifications for various science investigations Bust et al, 2007;Yin et al, 2006;Crowley et al, 2006]. In particular, IDA4D has been used to investigate the ionospheric response to major geomagnetic storms [Bust and Mitchell, 2008;Bust and Crowley, 2008], including the formation and evolution of SED.…”
Section: Ionospheric Data Assimilation Four-dimensionalmentioning
confidence: 99%